The Effect of Resilience Training on the Psychological Empowerment of ICU Nurses - Z Hezaveh; M Mardani Hamooleh; N Seyed Fatemi; SH Haghani (Iran University of Medical Sciences, 2020)
Background & Aims: Nurses work in stressful and challenging environments, which threaten their mental health. Among nurses, those in the intensive care units (ICUs) of hospitals are more likely to experience occupational, psychological, and physical stress compared to others. Due to their special working conditions (heavy workload, the need for a quick response to emergency situations, heavy responsibilities of care for critically ill patients, frequent contact with emotional situations, and being in unwanted situations to deliver bad news to the families of patients), these nurses are forced to endure more psychological pressures, which brings up the grave concern of their psychological empowerment being jeopardized. Psychological empowerment in nurses could increase organizational trust and commitment, thereby resulting in job satisfaction, productivity, participation in decision-making, provision of high-quality care, patient satisfaction, self-sufficiency, independence, self-confidence, responsibility, job control, and ultimately organizational effectiveness and occupational stress reduction. Therefore, it seems that nurses working in hospitals (especially in ICUs) need to improve their psychological empowerment. Meanwhile, resilience is one of the factors associated with the psychological empowerment of nurses. Resilience results in the better professional performance of nurses and is also a feature to help them adapt to the stresses of their work environment and improve their professional health. In the current century, nurses need to skillfully develop their resilience as it helps them to overcome their negative experiences and turn them into positive experiences. Therefore, nurses who are exposed to high stress levels could be trained to enhance their ability to overcome these pressures and gain a sense of worth. From a deeper perspective, resilience knowledge is a key to professional development in nursing. It has become increasingly important for nurses to be resilient as resilience with a preventative approach improves their mental health. Resilience training also seems to improve the psychological empowerment of nurses. The present study aimed to assess the effects of resilience training on the psychological empowerment of ICU nurses. Materials & Methods: This quasi-experimental study was conducted in the second half of 2019 on 96 nurses working in the ICUs of the teaching hospitals affiliated to Iran University of Medical Sciences. The subjects were selected via convenience sampling. The nurses were non-randomly assigned to two groups of experimental and control (48 ​​per each). Data were collected using a demographic data form to measure age, gender, economic status, marital status, employment status, work experience, and type of shifts. In addition, the psychological empowerment scale was used for data collection with the dimensions of sense of competence, independence, effectiveness, and meaningfulness. The validity of the scale was evaluated using the content validity method, and its reliability was confirmed at the Cronbachchr('39')s alpha coefficient of 0.84. Initially, pretest was performed on both groups. The resilience educational program was developed by the researcher based on concepts such as optimism, empathy, humor, problem-solving, coping with stress, self-efficacy, social adequacy, emotional management, and spirituality. The program was held for two hours per day for the experimental group during a two-day workshop. In each session, the presentation of the contents was performed in the form of a lecture with questions and answers, group discussions, and slide shows for the nurses. In addition, the nurses were provided with exercises to improve resilience, and their feedback was assessed during each session. The control group received no intervention. One month after the intervention, posttest was carried out on both groups. After the posttest on both groups, the resilience training contents were also provided electronically to the control group. This article was extracted from a research project approved by Iran University of Medical Sciences. During the research process, the ethical policies of the university were observed, including obtaining informed consent from the nurses. Data analysis was performed in SPSS version 16 using descriptive statistics (mean and standard deviation) and inferential statistics (Chi-square, independent and paired t-test, Fisherchr('39')s exact test, and analysis of covariance). Results: At the pretest stage, significant differences were observed in the scores of psychological empowerment and all its dimensions, with the exception of meaningfulness (P<0.05). At the posttest and after the control of the effects of the confounders, the scores of psychological empowerment and its dimensions were significantly higher in the experimental group compared to the control group (P<0.001). In the experimental group, the scores were significantly higher after the intervention compared to before the intervention (P<0.001), while the scores significantly decreased in the control group (P<0.001). Furthermore, the changes in the scores of psychological empowerment and its dimensions were significantly higher in the experimental group compared to the control group (P<0.001).     Conclusion: According to the results, resilience training could improve the overall psychological empowerment of the ICU nurses in the four dimensions of sense of competence, independence, effectiveness, and meaningfulness. Considering that nursing is a profession that may threaten psychological empowerment, the use of resilience-based training programs that are low-cost, available, and high-performance could enhance the psychological empowerment of the nursing staff in general and ICU nurses in particular and should be considered by nursing managers.